Protocol for an exploration of knowledge sharing for improved discharge from a mental health ward. Issue 9 (1st October 2014) - Rowley, Emma; Wright, Nicola; Waring, Justin; Gregoriou, Kyri; Chopra, Arun
Abstract : Introduction: Strategies to reduce hospital admissions for mental health service users have received vast amounts of attention, yet the transfer of care from hospital to the community has been ignored. The discharge process is complex, messy, disjointed and inefficient, relying on cross-agency and organisational working. Focusing on one acute mental health admission ward, we will investigate whether the discharge process for people with severe mental health problems can be enhanced through the creation, implementation and utilisation of a knowledge sharing proforma that is used on their admission to the ward. Methods and analysis: The project uses qualitative interviews to understand the complex processes associated with being admitted and discharged from inpatient mental health wards. Practitioners will be asked to identify and map the relevant stakeholders involved in admission and discharge, and discuss any problems with the process. The study team will work with clinicians to develop a knowledge collection proforma, which will be piloted for 2 months. Qualitative interviews will be carried out to collect reflections on the experiences of using the tool, with data used for further refinement of the intervention. Baseline and repeat quantitative measures will be taken to illustrate any changes to length of stay and readmission rates achieved as a result of the study. Ethics and dissemination: A key issue is that participants are able to comment frankly on something that is a core part of their work, without fear or reprise. It is equally important that all participants are offered the opportunity to develop and coproduce the knowledge collection proforma, in order that the intervention produced is fit for purpose and usable in the real world, away from a research environment. The study has received ethical approval from Nottingham University Business School ethics committee, and has all appropriate National Health Service research governance clearances.